The Dynamics of Cultural Transition - Colangelo, Aldo (Italian Canadiana, 2020)
The article is based on a 1991-92 research, published in Sole senza Sole (1998). In his book Colangelo retraced the journey and life of 110 Italian women, residing in Toronto. He followed the stages of their lives, successes and difficulties, including those arising from their retirement onwards. For these women the greatest difficulties began just when they could relax with their husbands and enjoy the well deserved retirement. After the death of their spouses these women often lived alone; they did not know how to drive; their children were adults and independent; they did not interact much with their neighbours: they lived in a neighborhood far from shops, supermarkets, churches, etc. This situation created an existential void, isolation and solitude, aggravated by long, unnerving climatic conditions and a silence that it is not golden nor a “blessed solitude!” In this article, Colangelo reflects on the dynamics of the cultural transition of the emigrant-immigrant, who encompasses two different experiences: first as one who leaves his country, and second as one who enters the country in which he or she has decided to settle.